Cross-sectional studies: Estudios transversales - Cvetković Vega, Aleksandar (2020)
Cross-sectional studies are epidemiological design which can be considered as descriptive or analytical designs depending on the general objective. This is a quickly and economical design and allows to calculate the prevalence of a condition. Also, the relationship of temporality between the exposition and the outcome is being measured simultaneously on a unique period, not being possible to identify a directionality in the temporality. When there is an analytic objective, the association measure used is the Prevalence Ratio (PR), specially when the prevalence of the outcome is more or equal to 10% or the Odds Ratio (OR) when that prevalence is lower. To quantify this association different regression models like Binomial log or Poisson log can be used, including generalized lineal models. If the association measure is OR, the most common used model is the multiple logistic regression.